Dissimilarity measurements and the size structure of ecological communities. Issue 12 (18th November 2013) - De Cáceres, Miquel; Legendre, Pierre; He, Fangliang; Faith, Daniel
Summary Measurements of community resemblance in ecology are often based on species composition, and the starting point for calculations is usually a site‐by‐species data table. However, resemblance measurements may not be sufficiently accurate when communities are described using species composition only. Characteristics such as the size of their constituting organisms are also important to understand community organization. Here, we provide a framework that generalizes conventional resemblance measurements by incorporating the size structure of the compared communities. We first introduce the concept of cumulative abundance profile, which generalizes traditional species abundance values, and describe how to calculate it. We then explain our approach to compare cumulative abundance profiles in community resemblance measurements and use a small simulation study to determine which resemblance coefficients appropriately deal with compositional and structural differences. After that, we present an illustrative example where we study the structural and compositional variation between and within six Douglas‐fir forest plots in British Columbia, Canada. According to our investigations, the generalizations we suggest for the percentage difference (alias Bray–Curtis dissimilarity) and the Ružička coefficients are appropriate to measure community resemblance in terms of size structure, species composition or both. Our framework allows community resemblance to be measured in terms of either size structure or species composition, or both. A broad range of applications is expected. In the case of terrestrial plant communities, potential applications include analyses of community dynamics and classification of vegetation.